A pesquisa colaborativa como espaço de formação continuada de professores do ensino fundamental : possibilidades a partir das perguntas dos estudantes - Mertins, Simone (2023)
This study aimed to answer the following research problem: How does the improvement of teaching practice occur, involving Collaborative Research in the continuing education of Elementary School teachers, in relation to the meanings and use of students' questions in investigative classrooms? Thus, the general objective of the research was to understand how the improvement of teaching practice occurs, involving Collaborative Research in the continuing education of Elementary School teachers, in relation to the meanings and use of students' questions in investigative classrooms. The research is characterized as qualitative Collaborative Research. Collaborative Research, conducted with teachers from a public school in a city in the metropolitan region of Porto Alegre, was conceived as a space for continuing education, in which teachers reflected on and put into practice actions related to teaching and learning based on students' questions. Initially, from March to August 2021, 33 Elementary School teachers participated, and the training meetings were held via Google Meet. In a second phase, which corresponded to the period from August to December 2021, the meetings were held in person at the school with 11 teachers. Questionnaires, semi-structured interviews, audiovisual recordings of online meetings, and audio recordings of face-to-face meetings were analyzed through Textual Discursive Analysis. From the analysis, the following categories emerged: i) How teachers value and use students' questions in the classroom; ii) Modifications of the use of students' questions in the classroom; and iii) Contributions of continuing education to the improvement of teaching practice of Elementary School teachers. Based on the results, the thesis is that Collaborative Research as a space for continuing education contributed to the improvement of teaching practice of Elementary School teachers by qualifying them to teach through questioning. The development of this study made it possible to think about new models of continuing education that prioritize teaching practice and reflection on action. Regarding students' questions, the research showed that it is possible to use students' questions in classes as a starting point for investigative activities.